2014
DOI: 10.4244/eijv10sta15
|View full text |Cite
|
Sign up to set email alerts
|

The National Infarct Angioplasty Project: UK experience and subsequent developments

Abstract: The UK had previously established a comprehensive strategy for in-hospital nurse-led thrombolysis for patients with ST-elevation myocardial infarction, with a growing use of pre-hospital thrombolysis by paramedical staff in the ambulance services. The National Infarct Angioplasty Project was sponsored by the government and examined the introduction of primary percutaneous coronary angioplasty (PPCI) in a variety of urban, rural and mixed communities. The project found that PPCI could be delivered within accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…NICOR data were drivers of the National Infarct Angioplasty Pilot Project (2004–2008), which influenced the government policy decision to recommend primary angioplasty as the default revascularisation treatment for patients with STEMI 58. NICOR data have also been important in deriving performance indicators to assist healthcare commissioners.…”
Section: Supporting National Initiativesmentioning
confidence: 99%
“…NICOR data were drivers of the National Infarct Angioplasty Pilot Project (2004–2008), which influenced the government policy decision to recommend primary angioplasty as the default revascularisation treatment for patients with STEMI 58. NICOR data have also been important in deriving performance indicators to assist healthcare commissioners.…”
Section: Supporting National Initiativesmentioning
confidence: 99%
“…In recent years, the widespread recognition of primary percutaneous coronary intervention (PPCI) as an evidence-based treatment strategy that can improve outcomes has led to both an increase in PPCI volume and a reduction in hospital mortality associated with STEMI [ 2 , 3 ]. A major driver to facilitate this has been the creation and implementation of organised PPCI networks that are able to triage and deliver patients directly to centres able to routinely provide this service both in- and out-of-hours [ 4 , 5 ]. Patients are subsequently generally cared for in a coronary-care unit (CCU), which has been shown to reduce mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The National Infarct Angioplasty Project has demonstrated the benefits of PPCI over thrombolysis for treatment of STEMI patients [ 7 ] and has led to the creation of PPCI centres across England. By 2013, some regions demonstrated that more than 95% of patients treated for STEMI received PPCI, compared with only 30% in the third quarter of 2008 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was rapid change and, by 2012–2013, over 95% of eligible patients received primary PCI. 22 Such regional audits will play a decisive role in measuring changes in strategies, monitoring performance and highlighting the associated improvements in outcomes. 22 …”
Section: Discussionmentioning
confidence: 99%